Critical Curriculum Studies : Education, Consciousness, and the Politics of Knowing - Au, Wayne (New York Routledge Taylor & Francis Group, 2012)
"Critical Curriculum Studies" brings together curriculum theory, critical educational studies, and feminist standpoint theory with practical examples of teaching for social justice to argue for a transformative curriculum that challenges existing inequity in social, educational, and economic relations. Making use of the work of important scholars such as Freire, Vygotsky, Hartsock, Harding, and others, "Critical
Include Reference, Bibliography and Index
Keywords: United States -- Critical pedagogy -- Education--Curricula--Social aspects